The Influence of Financial Management Policy and Financial Performance on Company Value - Gultom, Fuji Fiolin; Simanjuntak, Tessya; Geopani, Noprin; Afdhal, Apsyanaya (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
The purpose of this study is to see and analyze the influence of financial performance and management policies of the Company on the value of the company. This study conducted a literature review on ten research articles that discuss the Company's financial performance and management policies of the company. This study found that any measuring instrument and ratio that has been used by previous studies to measure the company's financial performance is the financial ratio. From several previous studies, financial ratios include liquidity ratios, profitability, solvency, and activity. The results of this study are, This study shows that investment decisions, capital structure, dividend policy, and financial performance such as profitability and efficiency have an effect on company value.